Penerapan model pembelajaran structured numbered heads untuk meningkatkan keterampilan berpikir flexibility dan originality pada pembelajaran ips kelas iv sekolah dasar - Erik Cristanto; Siti Istiyati; Sularmi Sularmi (Didaktika Dwija Indria, 2019)
Abstract. The purpose of this research is to improve flexibility and originality thinking skills in Social Sciences lessons through used Structured Numbered Heads learning model for 4th grade of elementary school student at Surakarta on 2018/2019 academic year. The subjects of this research were class teacher and 33 students from 4th grade of elementary school student. The procedure of this research consisted of two cycles, each of that cycles had 4 stages, namely planning, action, observation, and reflection. Data collection techniques used are interviews, observation, flexibility and originality thinking skills tests, and document studies technique. Data validity used is content validity and triangulation technique. Data analysis used is interactive analysis (Miles and Huberman models). The results of the research on flexibility thinking skills increased from initial condition was 21,79 (0%) to 66,73 (55%) in the first cycle, 87,30 (82%) in the second cycle. The results of the research on originality thinking skills increased from initial condition was 25,76 (0%) to 69,61 (55%) in the first cycle, 83,39 (82%) in the second cycle. Based on the results of this research, it was concluded that the flexibility and originality thinking skills of 4th grade elementary school students in social science leasson increased after the Structured Numbered Heads learning model was implemented.Keywords: flexibility thinking skills, originality thinking skills, social sciences lessons, Structured Numbered Heads learning model, elementary school